Failure prevention of plant and machinery - Hattangadi, A. A. (McGraw-Hill's AccessEngineering., 2004)
Based on the premise of 'Zero-Failure performance' and the aspiration for the same, this book introduces the general features and investigative methods for determining failures of mechanical and electrical equipment. It focuses on the degradation processes and highlights the failure modes and mechanisms, including the apparently trivial ones.